A Guerra e as Guerras Coloniais na África subsaariana (1914-1974) - Sérgio Neto (História Contemporânea, 2019)
The Great War and Colonial Wars in Sub-Saharan Africa (1914-1974) seeks to situate world conflicts especially that of World War I, in the larger landscape of colonized Africa, and does not shy away from capturing more particular, conflict-centred experiences Luso-Germanic, in the emigration, in the feminine condition and in the performance of the metropolitan Regiment of Infantry 14, of Viseu, Angola. For its part, another contribution will seek to establish bridges between the peace treaties of 1919 and the 'revival of territorial claims over southern Portuguese Africa'. On the idleness of these troubled times, of highlighting the writings on football and the use of the automobile in the exotic itineraries of such a vast and diversified Empire.